Identification of miRNAs involved in DRG neurite outgrowth and their putative targets. Issue 14 (2nd July 2017) - Motti, Dario; Lerch, Jessica K.; Danzi, Matt C.; Gans, Jared H.; Kuo, Frank; Slepak, Tatiana I.; Bixby, John L.; Lemmon, Vance P.
Abstract : Peripheral neurons regenerate their axons after injury. Transcriptional regulation by microRNAs (miRNAs) is one possible mechanism controlling regeneration. We profiled miRNA expression in mouse dorsal root ganglion neurons after a sciatic nerve crush, and identified 49 differentially expressed miRNAs. We evaluated the functional role of each miRNA using a phenotypic analysis approach. To predict the targets of the miRNAs we employed RNA‐Sequencing and examined transcription at the isoform level. We identify thousands of differentially expressed isoforms and bioinformatically associate the miRNAs that modulate neurite growth with their putative target isoforms to outline a network of regulatory events underlying peripheral nerve regeneration. MiR‐298, let‐7a, and let‐7f enhance neurite growth and target the majority of isoforms in the differentially expressed network. Abstract : Read the Commentary on this article at doi:10.1002/1873-3468.12736